Key factors in the strategic transformation of traditional food enterprises in China - LAU, Hui Ching (Institutional Knowledge at Singapore Management University, 2022)
The food industry is an important industry for China’s social development and one of the pillar industries of China's industrial economy. With the development of China’s urbanization, the victory of building a moderately prosperous society in all respects, and the continuous improvement of people’s living standards, consumer demand has become diversified and rationalized from “seeking for fullness” to “seeking for good”. In this context, the supplier of food products, that is, food companies, has become more competitive in market segments. With the continuous improvement of China's market openness, many top international food companies have flooded into the food industry. Coupled with the rapid development of local companies over the past few decades, there are a large number of competitors in the food industry, among which there are many international companies with a profound history of development, which has gradually reduced the living space of traditional food companies, especially small and medium-sized companies. Facing the changing consumer demand, fierce competition in the industry, and economic downward pressure from international trade frictions and public health crises, how to survive and develop under severe conditions has become a difficult problem for many small and medium-sized food companies. Exploring new growth models, seeking transformation and upgrading, and finding new growth engines for enterprise development have become the urgent tasks of traditional food companies. In the face of the challenges from market demand, market competition, and changes in the economic situation, traditional food companies can get a breakthrough opportunity only by breaking through the shackles of the original development model and reshaping their core competitiveness through enterprise strategic transformation within the. However, the current transformation and development path for traditional food companies is not clear. To find a suitable transformation and development path for traditional Chinese food companies, academics have to seriously consider the following questions: (1) What corporate factors will affect the transformation process of food companies? (2) Is it possible to build a data-tested influence factor analysis framework applicable to the transformation of traditional Chinese food companies? (3) Can the established analysis framework be applied in practice to provide guidance for the transformation and upgrading of our case company and other food companies? (4) Can the research and analysis of the case companies further optimize our analysis framework? In this study, literature research method, questionnaire survey method and case analysis method were comprehensively adopted to build a data-tested framework for the analysis of influencing factors applicable to the transformation of Chinese traditional food enterprises. First, sort out the related literature on the food industry and enterprise transformation, theoretically clarify the research context of enterprise transformation, and straighten out the theoretical logic of the related theories, influencing factors and research status of enterprise transformation. Secondly, based on the findings of literature review, this research combines the enterprise transformation theory proposed by Professor William B. Rouse in 2005 with the special elements of Chinese cultural background such as paternalistic management decision-making style and family business characteristics, to extract a driving factor analysis model suitable for the strategic transformation of Chinese food companies. Based on this model, this research puts forward research hypotheses. Third, select the Q Group who has distinctive Chinese characteristics as the case company, collect first-hand data in the company through questionnaires to test the hypotheses and model from a quantitative perspective. And then, also based on the model, the transformation process is analyzed through case study, and the rationality of the model is verified from the qualitative point of view. Finally, summarized the research conclusion and put forward the key factors the food companies need to focus on in the process of strategic transformation, and the pointed out the research limitations and future research direction, in the hope of the future to further optimize the analysis framework of enterprise transformation, to provide more guidance for the transformation and upgrading of traditional food companies. The main findings of this study are as follows: First, value defects have a significant positive impact on corporate transformation. When the management and employees realize the value defects of their employers, they will embrace the thought of supporting corporate managers to change and transform the business. Value defects can result in loss of value and reduced profitability, because of which the management will adjust their attention and reallocate resources accordingly. The more serious the existing defects of a company perceived by its management team and employees, the stronger the company's motivation for strategic transformation; the higher expectations the management and employees have for the upcoming crisis that their company will encounter. Second, plausible work process has a significant positive impact on the transformation of enterprises. The management and employees may check and modify their work processes and recognize their optimization to fulfill corporate strategic transformation, when the value defects of their companies are perceived. The research divided the work process into five sections: financial status, operational status, human resources status, marketing and sales status, and research and development status. The result showed that reasonable work processes will also positively affect the strategic transformation of enterprises. Third, management decisions making affect the relationship between work processes and corporate strategic transformation. The degree of influence by the improvement of work processes on the strategic transformation of enterprises will be determined by the problem-solving and decision-making ability of the leadership, management structures, and the characteristics of managers. To more be specific, flat management structure and action-oriented decision-making style can reinforce the impact of work process on corporate strategic transformation, but familial management will weaken the influence. First of all, all employees should strengthen their awareness of corporate value defects before a company embarks on the journey of strategic transformation. Secondly, the optimization of work processes will facilitate the success of corporate strategic transformation. Thirdly, revamping management personnel can help improve the effect of corporate transformation.